Les prépositions italiennes di et da et la préposition française de. Une étude contrastive dans un cadre cognitif - Kwapisz-Osadnik, Katarzyna (Neophilologica, 2018)
The aim of the article is to examine the functioning of Italian prepositions di and da and the French preposition de. Given their common Latin origin, it can be noted that some of the uses of the French preposition de are divided between at least two Italian prepositions. The author of the article briefly presents the state of the research in this field and then proposes a reflection in the context of cognitive linguistics. The functioning of the prepositions in question is presented in relation to the language image of the world, which is formed at the level of collective experience, in relation to both conceptual and linguistic levels, where the predication is determined (semantic invariant, usage preferences). It also refers to the discursive level, where the linguistic choices of the speakers are made.